Tumor budding for predicting prognosis of resected rectum cancer after neoadjuvant treatment - (:unkn) unknown (BMC, 2019)
BackgroundRectum cancer is a type of colorectal cancer. Its etiology and etiopathogenesis are similar to other colon diseases. We aimed to evaluate the tumor budding for predicting prognosis of resected rectum cancer patients.MethodsWe retrospectively collected the data of 75 operated rectum adenocarcinoma patients who were treated neoadjuvant chemoradiotherapy between 2013 and 2018 in Umraniye Research and Training Hospital and Acbadem University Medical Oncology Outpatient Clinic. Tumor budding was investigated as a prognostic factor for disease-free survival.ResultsThis study included 75 rectum cancer patients and 51 were male (68%). Median age was 56 (range 19 to 77years). There were 29 (39%) and 46 (61%) patients in tumor budding low-intermediate and high groups respectively. In multivariate analysis, tumor budding was found to be an independent prognostic factor for disease-free survival (p=0.00).ConclusionsAccording to our study, having high tumor budding suggests a high likelihood of relapse. Therefore, we might need additional follow-up protocol in these patients.
Keywords: Tumor budding; Prognosis; Rectum cancer; RISK; RECURRENCE; SURVIVAL; MARKER; SYSTEM